METHODOLOGICAL APPROACHES TO DETERMINING THE PRODUCT RANGE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS FOR THE TREATMENT OF OCCUPATIONAL DISEASES OF THE MUSCULOSKELETAL SYSTEM - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Елена Владимировна Часовских; Наталья Степановна Черных (Медицина в Кузбассе)
The goal is to develop methodological approaches to determining the product range of nonsteroidal anti-inflammatory drugs (NSAIDs) for the treatment of occupational diseases of the musculoskeletal system of coal industry workers.